A Numerical Perspective on Solving Non-Linear Equations: Newton Vs. Bisection - Bhatt, Mohan Raj; Dhungana, Hem Lal; Dhakal, Gita Ram (Academic Journal of Mathematics Education, 2024)
The purpose of this paper is to review the methods of solving non-linear equations and compare them for their procedure and suitableness for solving. The study reviewed two of methods Newton’s method and Bisection method from various methods to solving nonlinear equations. The table and graphs were used to compare them and found that Newton method is measured the best due to its speedy and precise convergence to the roots. On the other hand, the Bisection method, though slower in reaching the roots compared to the Newton method, ensures convergence to the root regardless of the number of iterations.